Development Strategy 0f Local Food Diversification - Imelda, Imelda; Kusrini, Novira; Hidayat, Rakhmad (JEJAK: Jurnal Ekonomi dan Kebijakan, 2017)
The purpose of this research is to develop strategies that can be applied in the development of local food diversification in West Kalimantan. The data used are primary data and secondary data. Variables examined included internal factors (strengths and weaknesses) and external factors (opportunities and threats) in the development of local food diversification in West Kalimantan. Data analysis were conducted in qualitative descriptive to describe the pattern of food consumption in West Kalimantan and continued with a SWOT analysis to carry out the development strategy of the local food diversification in West Kalimantan. The analysis result showed that the strategy for the development of local food diversification in West Kalimantan is SO strategy (Strengths - Opportunities) those are: 1) the increase in synergy between the government and the micro, small and medium enterprises for the development of local food products, 2) the utilization of communications and market information system in improving the marketing of local food products on micro, small and medium enterprises, and 3) the utilization of unutilized agricultural land to improve the quality and quantity of local food products.